AN ANALYSIS OF GRAMMATICAL ERRORS ON STUDENTS’ WRITING NARRATIVE TEXT OF SECOND GRADE AT SMA NEGERI 2 HILIMEGAI - Widarlina Laia (Research on English Language Education, 2024)
This research aimed at analyzing grammatical errors on students’ writing narrative text of second grade at SMA Negeri 2 Hilimegai academic year 2022/2023. This research was designed by using qualitative descriptive method. In analyzing the data, the researcher used theory of Miles et al. The source of data in this study was taken from students’ writing of narrative text. The members of participant consist of 17 students. The data of this study were grammatical errors in narrative text. The result of the research showed that there were 337 grammatical errors made by students from six categories of grammatical errors types, namely; error in using past tense was 132 errors, error of action verb was 108 errors, error in building noun phrase was 48 errors, error of pronoun 32 errors, error of adverb 11 errors and time connection 6 errors. It can be concluded that in writing narrative texts there are several grammatical errors made by the second grade students of SMA Negeri 2 Hilimegai academic year 2022/2023. It is suggested that teachers use the most appropriate creative teaching methods and techniques to make students interested in learning English.